Study of Crypto Currency in Indonesia - Erwanto, Erwanto; Santoso, Aris Prio Agus (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
Currency as a legal means of payment is needed in domestic and international economic activities to achieve the social welfare of Indonesian society as a whole. Regulations regarding the nature and price of currency are contained in Article 23 B of the 1945 Constitution of the Republic of Indonesia. To ensure legal certainty and legal protection, another law was enacted, namely Law Number 7 of 2011 concerning currency. The aim of this research is to analyze the use of crypto money as a means of payment in Indonesia. This research uses a statutory approach and a conceptual approach. Data analysis uses qualitative analysis techniques to test the validity of the data in this research by looking for existing reference sources. Based on the research results, it shows that a series of legal regulations in Indonesia regarding digital crypto money show the government's awareness in creating the rule of law within the scope of the economic ecosystem in the digital era. So this is something special for Indonesia as a country that is serious about protecting its people in cryptocurrency transactions as assets or commodities (crypto assets). However, there are conflicting perspectives in viewing the position of digital crypto money. Bank Indonesia places it as digital money (virtual currency) so its use is prohibited as a means of payment. As for the Ministry of Trade, through Bappebti, it places crypto digital money (cryptocurrency) as a digital asset or commodity so that based on normative provisions it is allowed to be traded on the Futures Exchange. Therefore, the government needs to harmonize the law in positioning crypto digital money.